Respostas
respondido por:
0
a+b = 2
-a + 3b= 8
3b = 8 + a
b = (8+a)/3
na equação a +b =2 , em vez de você colocar o b, como vc sabe que b= (8+a)/3 você troca b,por ele.
a+(8+a)/3 = 2
4a+8/3 = 2
4a + 8 = 6
4a = -2
a = -2/4
a = -1/2
-1/2 + b = 2
b = 2 -1/2
b = 2/3
-a + 3b= 8
3b = 8 + a
b = (8+a)/3
na equação a +b =2 , em vez de você colocar o b, como vc sabe que b= (8+a)/3 você troca b,por ele.
a+(8+a)/3 = 2
4a+8/3 = 2
4a + 8 = 6
4a = -2
a = -2/4
a = -1/2
-1/2 + b = 2
b = 2 -1/2
b = 2/3
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás